Parenteral Nutrition Prescribing and Order Review Safety Study: The Need for Pharmacist Intervention. (4th December 2020) - Kraft, Michael D.; Tucker, Anne M.; Durfee, Sharon M.; Jones, Todd; Guenter, Peggi; Banko, David E.; Ayers, Phil; Boullata, Joseph; Raymond, Erica; Sacks, Gordon S.
Abstract: Introduction: Errors have been reported in the literature to occur at each step of the parenteral nutrition (PN) use process, necessitating standardized processes, clinician competence, and open communication for those involved. This study was performed at Central Admixture Pharmacy Services (CAPS®) in collaboration with the American Society for Parenteral and Enteral Nutrition (ASPEN) with the purpose to study the need for and success of PN pharmacist interventions. Methods: A survey was developed and sent to all CAPS customers for study enrollment and to identify their demographic and practice characteristics. For those enrolled, CAPS pharmacists reviewed every PN order in a 1‐month period using an error/intervention tool to capture data on prescription elements requiring intervention, along with acceptance of that intervention. Results: Two hundred thirty‐two unique CAPS customers (23% response rate) participated in the study, representing 37, 634 unique PN prescriptions. Two hundred forty‐eight PN prescriptions (0.66%) from 59 customers required ≥1 intervention. The top 3 intervention types were electrolyte dose clarification, calcium/phosphorus incompatibility, and amino acid dose clarification. A greater number and percentage of interventions were required for neonatal prescriptions, as compared with adult and pediatric prescriptions. No significant difference was found in many of the other customer characteristics. Conclusion: This study supports the need for institutions to develop systems to comply with published PN safety recommendations, including knowledgeable and skilled pharmacists to complete the order review and verification steps for this high‐alert medication.